2006
DOI: 10.1093/mutage/gel039
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and molecular biomonitoring of a Portuguese population exposed to pesticides

Abstract: Widespread use of pesticides in agriculture represents a threat not only to the environment but also to human populations exposed to them. Many of these compounds are capable of inducing mutations in DNA and lead to several diseases including cancer. In the present study, cytogenetic damage in peripheral lymphocytes from 33 farmers of Oporto district (Portugal) exposed to pesticides was evaluated by means of micronuclei (MN), sister chromatid exchange (SCE) and chromosomal aberrations (CA). In addition, effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
37
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 64 publications
8
37
0
8
Order By: Relevance
“…This can be due to the misconception that non-applicators are not as exposed as applicators. Our study revealed similar frequencies in the Comet assay considering applicators and non-applicators in agreement with previous research (Costa et al, 2006). Therefore, occupational exposure to pesticides can fluctuate in time and the skin constitutes a significant exposure route of absorption mainly in agriculture (Jakubowski & Trzcinka-Ochocka, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This can be due to the misconception that non-applicators are not as exposed as applicators. Our study revealed similar frequencies in the Comet assay considering applicators and non-applicators in agreement with previous research (Costa et al, 2006). Therefore, occupational exposure to pesticides can fluctuate in time and the skin constitutes a significant exposure route of absorption mainly in agriculture (Jakubowski & Trzcinka-Ochocka, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…An increase in micronuclei was seen in pesticide-exposed people who did not wear protective gloves (Bolognesi et al, 2002). At the same time, increases in the frequencies of chromosomal aberrations and micronuclei have been found in some studies where the population exposed to pesticides wore no protection during work activities (Costa et al, 2006) or little or no protective clothes (Dulout et al, 1985). Interestingly, several studies that reported a majority of workers using protective measures (>60%) concluded that the results were negative (Bolognesi et al, 2004;Pastor et al, 2001 andPiperakis et al, 2003 and, suggesting the importance of PPE for preventing exposure.…”
mentioning
confidence: 94%
“…Many investigations have focused on the evaluation of genotoxicity of pesticides in occupational or environmental settings using different methods (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). It has been reported that exposure to environmental contaminants including pesticides causes major pathological effects in the human male reproductive system as well as that of experimental animals (13,14).…”
mentioning
confidence: 99%
“…The tests performed on cell cultures and/or in the animal model indicated that agrochemicals could significantly increase DNA damage. Furthermore, human biomonitoring studies on the genotoxicity of pesticides, assessed with the micronucleus test, the sister-chromatid exchange (SCE) assay, the chromosomal aberration (CA) test, and the comet assay (Augusto et al 1997;Coskun et al 2011;Costa et al 2006Costa et al , 2007Gomez-Arroyo et al 2000;Martínez-Valenzuela et al 2009;Paiva et al 2011;Ü ndeger and Başaran 2002), have shown that occupational exposure to such chemicals could induce a significant increase in genetic damage.…”
Section: Discussionmentioning
confidence: 99%